Endocarpo-Xanthocarpion tominii all. nov. and Caloplacetum albolutescentis ass. nov., a new syntaxa of lichen communities from loess outcrops in southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The new alliance Endocarpo-Xanthocarpion tominii all. nov. and association Caloplacetum albolutescentis ass. nov. (class Psoretea decipientis Mattik). in loess outcrops of southern Ukraine are described as new for science. The ecological peculiarities of the new lichen association are showed. The syntaxonomic table is given in this paper. The list of the lichens and lichenicolous fungi (42 species) of loess outcrops is provided.
Keywords: Endocarpo-Xanthocarpion tominii, Caloplacetum albolutescentis, Psoretea decipientis, association, syntaxonomic table, lichens.